2011
DOI: 10.1016/j.jssc.2011.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure and conductivity of sulfate and phosphate doped SrCoO3

Abstract: In this paper we report the successful incorporation of sulfate and phosphate into SrCoO 3 leading to a change from a 2H-to a 3C-perovskite polymorph. Structural characterization by neutron diffraction showed extra weak peaks related to oxygen vacancy ordering, and these could be indexed on an expanded tetragonal cell, containing two inequivalent Co sites, similar to previously reported for Sb doped SrCoO 3 .Conductivity measurements on the doped systems showed a large enhancement compared to the undoped hexag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…In particular, we have shown that the partial substitution of these oxyanions at the In/Sc site in Ba 2 (In/Sc) 2 O 5 leads to the introduction of disorder on the oxygen sublattice and a corresponding enhancement in the low temperature ionic conductivity [14][15][16][17][18]. In terms of electronic conducting materials, we have also reported the successful incorporation of silicate, phosphate and sulphate into SrMO 3 (M = Co, Mn), leading to a large enhancement in the electronic conductivity [19,20]. In these latter examples, this large enhancement in the conductivity could be explained by a change from a 2H-perovskite (containing face sharing of octahedra) to a 3C-perovskite (containing corner sharing of octahedra).…”
Section: Introductionmentioning
confidence: 70%
“…In particular, we have shown that the partial substitution of these oxyanions at the In/Sc site in Ba 2 (In/Sc) 2 O 5 leads to the introduction of disorder on the oxygen sublattice and a corresponding enhancement in the low temperature ionic conductivity [14][15][16][17][18]. In terms of electronic conducting materials, we have also reported the successful incorporation of silicate, phosphate and sulphate into SrMO 3 (M = Co, Mn), leading to a large enhancement in the electronic conductivity [19,20]. In these latter examples, this large enhancement in the conductivity could be explained by a change from a 2H-perovskite (containing face sharing of octahedra) to a 3C-perovskite (containing corner sharing of octahedra).…”
Section: Introductionmentioning
confidence: 70%
“…Further work showed that this doping strategy could also be extended to potential electrode systems, with Si, P doping into SrMO 3-y (M=Mn, Co) shown to enhance the electronic conductivity, associated with a conversion from a hexagonal perovskite system to a cubic perovskite system [19,20] In this paper, we extend this oxyanion doping work to examine the potential synthesis of used to demonstrate phase purity, as well as for preliminary structure determination. For the latter, the GSAS suite of programs was used [24].…”
Section: Introductionmentioning
confidence: 95%
“…19), (La,Sr)(Co,Fe)O 3−δ (refs 20, 21) and Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ 422, which are claimed to exhibit high ORR activity in the intermediate temperature range 600–750 °C because of their relatively high mixed conductivities2324. The perovskite structure of SC, which is favoured for ORR, is usually stabilized by partial B -site substitution with high oxidation-state cations25, such as Nb2627, Mo28, Sb2930 and P3132, and these cations lead to low area-specific resistances (ASRs) at reduced temperature272829313334. Besides the single doped SCs, Zhou et al 10.…”
mentioning
confidence: 99%